A review of railway transportation in Central Asia for corridors and the revival of the Great Silk Road - Mukhamedova, Ziyoda; Mukhamedova, Dilbar; Fuzailova Gоvhar; Ergasheva, Zahro; Yakupbaey, Khamid (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This review examines the state of railway transportation in Central Asia within the context of the Silk Road initiative, tracing its origins from the United States’ New Silk Road strategy. Despite recent setbacks, the Silk Route has become a crucial geopolitical tool for military, political, and economic interests, with corridors like Kazakhstan’s Terminal and the China-Kyrgyzstan-Uzbekistan-Afghanistan route identified for potential revitalization. Uzbekistan, particularly in the China-Kyrgyzstan-Uzbekistan corridor, emerges as pivotal for advancing the Silk Road initiative. A comprehensive analysis of data collection methodologies employed in studying these corridors is also included to ensure the reliability and validity of the findings. Employing a multifaceted methodology, including quantitative analysis of infrastructure metrics, case studies of specific projects, a literature review synthesizing existing knowledge, and comparative analysis drawing parallels and contrasts, this study explores opportunities and challenges in enhancing these corridors, aiming to contribute to the broader strategy’s rejuvenation in Central Asia. By analyzing current conditions and proposing improvements, the research seeks to optimize railway transport, aligning with the Silk Road’s historical significance in the contemporary geopolitical landscape.